Fluorescence microscopy-based RNA interference screening - Gunkel, Manuel; Beil, Nina; Beneke, Jürgen; Reymann, Jürgen; Erfle, Holger (Advanced fluorescence microscopy, 2015)
Using RNAi interference (RNAi), it is possible to study the effect of specific gene knockdowns in mammalian cells. In this protocol we present the automated preparation of “ready to transfect” multiwell plates and cell arrays, on which cells can be grown which are then reversely transfected with one type of siRNA in every individual well or spot. Additionally, different microscope types for screening approaches are compared and considerations about the information workflow are made.